1991
DOI: 10.2172/138189
|View full text |Cite
|
Sign up to set email alerts
|

In situ changes in the moisture content of heated, welded tuff based on thermal neutron measurements

Abstract: IMSIER t> flux of condensed water through fractures, fracture flow carried this water away before matrix imbibition could detectably increase matrix moisture content below the boiling zone. Numerical modeling indicated that the re-wetting of the dried-out zone was dominated by the binary diffusion of water vapor through fractures. Saturation gradients in the rock matrix resulted in relative numidity gradients which drove water vapor (primarily along fractures) back to the driedout zone where it condensed along… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1991
1991
1995
1995

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 2 publications
(2 reference statements)
0
5
0
Order By: Relevance
“…The models proposed below are, to a large extent, similm _to the starting conceptual model shown in the Introduction because the re,_ults described here and in Ramirez et al (1990) can be interpreted in a manner consistent with the conceptual model shown in the Introduction. The most significant modifications to the pretest conceptual understanding concerned the contribution of the gas phase to rewetting of the fractured rock mass.…”
Section: Conceptual Models For Drying and Rewetting Behaviormentioning
confidence: 67%
See 3 more Smart Citations
“…The models proposed below are, to a large extent, similm _to the starting conceptual model shown in the Introduction because the re,_ults described here and in Ramirez et al (1990) can be interpreted in a manner consistent with the conceptual model shown in the Introduction. The most significant modifications to the pretest conceptual understanding concerned the contribution of the gas phase to rewetting of the fractured rock mass.…”
Section: Conceptual Models For Drying and Rewetting Behaviormentioning
confidence: 67%
“…Other data in Ramirez et al (1990) show that relatively small changes occurred during the power rampdown phase. Figure 2-3 shows the changes in mnisture content measured 100 days after the heater was turned off (day 301) and the rock temperatures had recovered to within a few degrees of initial conditions.…”
Section: Sample Of Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Consequently, they did not have the same time resolution as the TCP data, which were measured every 30 minutes. These observed features could be explained by the gravity effect as described for neutron measurements at other locations (Ramirez and Carlson, 1990). Accordingly, as temperatures increased, the evaporation rate of pore water wouirf increase.…”
Section: Field-test Resultsmentioning
confidence: 59%